2020
DOI: 10.29100/jipi.v5i1.1518
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Pemrograman Dasar di SMK Muhammadiyah 1 Padang

Abstract: 2) ABSTRAK Salah satu permasalahan yang ada pada SMK Muhammadiyah 1 Padang adalah pimpinan sekolah belum mengetahui model pembelajaran apa yang sesuai sehingga dapat berpengaruh terhadap hasil belajar siswa. Berbagai strategi pembelajaran telah dilakukan, namun belum sesuai dengan yang diharapkan. Hal ini diindikasikan dengan rendahnya hasil belajar siswa khususnya pada mata pelajaran pemrograman dasar. Peneliitan ini bertujuan untuk mengetahui apakah terdapat perbedaan hasil belajar antara siswa yang memperol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…The results of hypothesis testing also confirm a significant effect of PjBL on learning outcomes. This is supported by research findings from Guo, et al ( 2020), ( 2021), (Refualu & Suriani, 2021), (Mulyono & Agustin, 2020), (Ningsih et al, 2022), and (Iswantari, 2021) The results showed that project-based learning had a moderate to large positive effect on students' academic achievement compared to traditional teaching. (Fahrezi et al, 2020) in their research demonstrate that learning using the Project-Based…”
Section: Discussionsupporting
confidence: 72%
“…The results of hypothesis testing also confirm a significant effect of PjBL on learning outcomes. This is supported by research findings from Guo, et al ( 2020), ( 2021), (Refualu & Suriani, 2021), (Mulyono & Agustin, 2020), (Ningsih et al, 2022), and (Iswantari, 2021) The results showed that project-based learning had a moderate to large positive effect on students' academic achievement compared to traditional teaching. (Fahrezi et al, 2020) in their research demonstrate that learning using the Project-Based…”
Section: Discussionsupporting
confidence: 72%
“…In essence, the main purpose of conducting this research is to find out whether there is an influence of the learning modelProject Based Learning on the learning outcomes of class VIII students at Tri Sakti Lubuk Pakam Private Middle School (Mulyono & Agustin, 2020) . So it can be concluded that the learning modelProject Based Learning can improve the learning outcomes of class VIII students at Tri Sakti Lubuk Pakam Private Middle School.…”
Section: Discussionmentioning
confidence: 99%
“…Model pembelajaran ini merupakan model pembelajaran inovatif yang melibatkan kerja proyek dimana peserta didik bekerja secara mandiri dalam mengkonstruksi pembelajarannya dan mengkulminasikannya dalam produk nyata [9]. Diperkuat adanya penerapan model pembelajaran berbasis proyek ini mempunyai pengaruh terhadap hasil belajar siswa pada mata pelajaran pemrograman dasar [10]. Langkah Pembelajaran berbasis proyek (Project Based Learning) diantaranya yaitu (1) pembelajaran dimulai dengan pertanyaan esensial, yaitu pertanyaan yang dapat memberi penugasan siswa dalam melakukan suatu aktivitas.…”
Section: Pendahuluanunclassified